Activity patterns at the Arctic Circle: nocturnal eagle owls and interspecific interactions during continuous midsummer daylight. (18th July 2018) - Eriksen, Ane; Wabakken, Petter
Abstract : Circadian rhythms result from adaptations to biotic and abiotic environmental conditions that cycle through the day, such as light, temperature, or temporal overlap between interacting species. At high latitudes, close to or beyond the polar circles, uninterrupted midsummer daylight may pose a challenge to the circadian rhythms of otherwise nocturnal species, such as eagle owls Bubo bubo . By non‐invasive field methods, we studied eagle owl activity in light of their interactions with their main prey the water vole Arvicola amphibius, and their competitor the white‐tailed eagle Haliaeetus albicilla during continuous midsummer daylight on open, treeless islands in coastal northern Norway. We evaluated circadian rhythms, temporal overlap, exposure, and spatial distribution. The owls maintained a nocturnal activity pattern, possibly because slightly dimmer light around midnight offered favourable hunting conditions. The eagles were active throughout the 24‐h period as opposed to the strictly diurnal rhythm reported elsewhere, thus increasing temporal overlap and the potential for interference competition between the two avian predators. This may indicate an asymmetry, with the owls facing the highest cost of interference competition. The presence of eagles combined with constant daylight in this open landscape may make the owls vulnerable to interspecific aggression, and contrary to the available literature, eagle owls rarely exposed themselves visually during territorial calls, possibly to avoid detection by eagles. We found indications of spatial segregation between owls and eagles reflecting differences in main prey, possibly in combination with habitat‐mediated avoidance. Eagle owl vocal activity peaked in the evening before a nocturnal peak in visual observations, when owls were active hunting, consistent with the hypothesis of a dusk chorus in nocturnal bird species. The owls may have had to trade‐off between calling and foraging during the few hours around midnight when slightly dimmer light reduced the detection risk while also providing better hunting conditions